Instantaneous room temperature bonding of a wide range of non-silicon substrates with poly(dimethylsiloxane) (PDMS) elastomer mediated by a mercaptosilane1. Issue 13 (7th July 2015) - Wu, Wenming; Wu, Jing; Kim, Jae-Heon; Lee, Nae Yoon
<x xml:space="preserve">Abstract</x> Instantaneous and robust bonding of various non-silicon substrates with PDMS was realized at room temperature within 12 to 17 min by mercaptosilane coating.